Heart-rots in Relation to Management of Sal - Bakshi, B. K. (Indian Forester, 1957)
Sal (Shorea robusta) in its extensive and varying habitat in India, suffers from heart-rot due to three major fungi, namely Fomes caryophylli, Hymenochaete rubiginosa and Fomes fastuosus, which cause serious economic loss. Trees between 15 and 35 years are mostly susceptible to attack by heart-rot fungi, whose entry into trees occurs through wounds from various causes some of which are physiogenic, like fire and frost and others mechanical. Affected trees are not killed, since the living sapwood is not normally attacked by these fungi, but the merchantable heartwood is decayed and lost. Such trees may appear quite healthy and complete the normal period of rotation. The symptoms manifested by trees attacked by the three heart-rot fungi, the nature of decay caused by them and their mode of spread are described. In many cases, the external symptoms are absent on trees containing heart-rot, so that diagnosis of such trees with hidden decay becomes difficult and leads to faulty marking during fellings. To control or reduce the incidence of heart-rot in high forests, the crop should be nursed during the critical period of susceptibility by sound silviculture, which includes protection from fire injury by control burning and manipulation of the overhead canopy to prevent frost and suppression. Thinnings and selection fellings should be carried out with a view to stand-improvement. All diseased trees should be removed during fellings to prevent further loss in nett volume recovery and spread of decay to the residual crop. A second marking may be necessary after felling is completed when trees with hidden decay become evident. Such trees and also those damaged during fellings should be removed. During fellings, injury to the standing crop from falling trees should be prevented by lopping the side branches of the latter if they are many, thick and spreading. Infected stumps should not be coppiced. Standards should be selected from healthy trees free from any symptoms of heart-rot. In moribund sal, dry felling at short intervals is desirable. Felling age in forests containing high incidence of heart-rot should be lowered. The forest pathological considerations in the management of coppice sal forests in the Southern Circle, West Bengal, are separate from those stated above. These forests are worked on a technical rotation of 10 years for fuelwood. Due to continued maltreatment to which these forests were subjected in the past, the incidence of decayed stumps is high. Any attempt to raise the rotation of these forests will be disastrous since the decay will progress from the stump into the tree when the heartwood develops. High forests in these areas can be raised from seeds. The seedling crop will then replace the existing coppice, the stumps of which may be prevented from further coppicing by mechanically extracting them, or by killing them with a poison.